Design and Development of an Android-Based Monitoring Application for the Poltekad Weapons Warehouse Using Generative Artificial Intelligence: Telekomunikasi Militer - Kharis Setiaji; Imam Ashar; Choirul Rio Prabowo (Pustaka Poltekad, 2026)
The management of the weapons warehouse within the Army Polytechnic (Poltekad) plays a crucial role in maintaining personnel security and training readiness. However, a persistent obstacle is the manual or semi-digital recording process. This slows down data collection, makes it prone to errors, and makes it difficult for officers to quickly submit reports to superiors. Based on these issues, this research developed a solution in the form of an Android-based monitoring application equipped with generative AI technology. The goal is simple: to facilitate real-time and intelligent weapons monitoring. Using a prototype development method, this system is designed not only to record incoming and outgoing weapons data but also utilizes AI to automatically compile daily narrative reports. The end result is that this application is proven to be effective, weapons stock data is more accurate, and administrative work for officers is significantly reduced thanks to the AI's automatic reporting feature.